Healing Effects of Platelet-Rich Plasma on Peripheral Nerve Injuries. Issue 1 (January 2017) - Bastami, Farshid; Vares, Peyman; Khojasteh, Arash
Abstract : Abstract: Regeneration of peripheral nerve injuries (PNIs) has been a major challenging issue in regenerative medicine and tissue engineering. Inferior alveolar nerve and lingual nerve injuries are the major difficulties and complications of oral surgeries following dental implant placement, etc. The aim of this study was to systematically review the effects of platelet-rich plasma (PRP) on the regeneration of PNIs. Medline NCBI databases were searched for related articles up to and including May 2016. Being published in English papers, use of PRP in peripheral nerve regeneration, in vivo studies, and having histological evaluations was the inclusion criteria. Seventeen papers were selected according to the inclusion and exclusion criteria, and categorized regarding PNIs types including cut or crushed injuries. The effects of using PRP only or in combination with cells on the functional recovery and histological assessments are discussed and compared with the other treatments such as autologous nerve graft, acellular nerve allograft, and synthetic nerve conduits. The authors also clarified the perspectives in the current field. Consequently, PRP demonstrated positive effects on healing of the nerve function as well histological improvements in cut nerve PNIs model; however, more studies in the field of crushed nerves are needed to arrive at an evidence-based conclusion.